Preparation method for novel NS5A inhibitor medicine - HUANG HU; HU HAIYANG; QI XIAOQING; LI ZEBIAO; GU WENCHAO; LIN YANFENG (2015)
The invention discloses a preparation method for novel NS5A inhibitor medicine. The preparation method includes the steps that step1, (1R, 3S, 4S)-3-(6-bromine-1H-benzimidazole-2-base)-2- azabicyalo (2.2.1) heptane-2-carboxylic acid tert-butyl ester serves as raw materials and reacts with bis (pinacolato) diboron under the action of a metal catalyst to obtain an intermediate L1; 1-(7-bromine-9,9-difluoro-9H-fluorene-2-base)-2-phenacyl chloride and (6S)-5-azaspiro (2.4) heptane-5,6-dicarboxylic acid 5-benzyl ester react under the action of a base to obtain an intermediate L2; the intermediate L1 and the intermediate L2 react under the action of a metal catalyst to obtain an intermediate L3; the intermediate L3 and an amine reagent react in a cyclization mode to obtain an intermediate L4; a protecting group is removed from the intermediate L4 under the action of methanesulfonic acid, so that an intermediate L5 in a mesylate form is obtained; the intermediate L5 and MOC valine react under the action of a condensing agent to obtain a Ledipasvir finished product. The process route is short, the preparation technology is simple, the intermediates are easy to control, and the reaction yield is high.